Pengaruh makroekonomi terhadap imbal hasil obligasi Indonesia - Insan Baihaqqy, Mochammad Rizaldy; Ikhsan, Sugiyanto; Sukmayana, Dodi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Investment is integral to improving a country's economy; the more investors who invest in a country, the more direct development activities will run well. Interestingly, there is an investment sector, namely bonds, which are attractive to be purchased by both foreign and local investors. Various studies provide various conclusions on the variables that affect bond yields. Inflation, interest rates and exchange rates will be used in this study as macroeconomic variables from 2010 to 2020. This study uses a quantitative methodology to investigate the relationship between bond yields and macroeconomic conditions. The research findings show that inflation, currency exchange rates, and interest rates do not affect bond yields. This indicates that macroeconomic changes have no impact on bond yields.